Fundamental lines of the Justice reform in Spain - Carretero González, Cristina (Razón y fe, 2018)
Justice in Spain is in need of reforms. The current Minister of Justice, Alberto Ruiz-Gallardón, has undertaken a series of institutional, structural and legislative reforms that, if successfully completed, will change the face of our current justice system. The criteria for this profound reform are, on the one hand, streamlining and equal opportunities in the ordinary practice of justice and, on the other, the reactivation of the economy. Time will tell if Justice as a public service will benefit or not.